Changes in Fecal and Colonic Mucosal Microbiota of Patients with Refractory Constipation after a Subtotal Colectomy. Issue 2 (February 2015) - Feng, Xiaobo; Su, Yong; Jiang, Jun; Li, Ning; Ding, Weiwei; Wang, Zhiming; Hu, Xionghui; Zhu, Weiyun; Li, Jieshou
The purpose of this study was to investigate the changes in gut microbiota of patients with refractory constipation 6 months after a subtotal colectomy. Feces and mucosal samples of five healthy volunteers and 17 patients with refractory constipation before and six months after subtotal colectomy were collected. Denaturing gradient gel electrophoresis (DGGE) and polymerase chain reaction techniques were used for quantitative analysis of main bacterial groups and archeal methanogens. No significant differences were found in the DGGE profiles among the three groups. After subtotal colectomy, a significantly decreased similarity coefficient was observed in the fecal. The Shannon diversity indices had no significant differences among the three groups. The numbers of predominant bacteria (Bacteriodetes, Clostridium coccoides group, and Clostridium leptum group) did not significantly change in patients before and after surgery compared with healthy control subjects, and the number of total bacteria, Firmicutes, Bacteriodetes, and Clostridium leptum group bacteria in the feces decreased after surgery. However, the numbers of these bacteria remained the same in mucosa from postoperative patients. The numbers of Bifidobacteria and Lactobacilli in feces and the number of Bifidobacteria in mucosa were significantly lower in preoperative compared with healthy control subjects and increased after the surgery. The number of methanogens in the mucosa was decreased in preoperative patients but returned to normal levels postoperatively. In conclusion, although there was no difference in the structure of the predominant bacteria between refractory constipated patients and healthy control subjects, the number of probiotics ( Bifidobacteria and Lactobacilli ) was significantly lower in refractory constipated patients. However, subtotal colectomy can significantly normalize the number of intestinal flora.